Monthly Variations on Physicochemical Parameters of a Freshwater Ecosystem of Kurichi Lake, Coimbatore District, Tamil Nadu, India - S, Christobher.; S, Ananthi.; P, Priyadharshini.; M, Kavitha.; V, Mahalakshmi.; S, Somasundaram; P, Athif; K, Muhammed Nisar. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study investigated the water quality of Kurichi Lake in Coimbatore District, Tamil Nadu, India, by assessing the physicochemical parameters of its surface water over an eight-month period. Water samples were analyzed using standard laboratory procedures to examine the influence of seasonal variations on key water quality indicators. The parameters studied included temperature, pH, turbidity, conductivity, hardness, TDS, phosphate, magnesium, chloride, calcium, sulfate, nitrate, dissolved oxygen (DO), biological oxygen demand (BOD), and chemical oxygen demand (COD). The results revealed that some of the parameters fell within permissible limits. Many exceeded the established threshold for safe water quality. Specifically, the water quality of Kurichi Lake was found to be just below the pollution threshold, rendering it unsuitable for both potable use and the support of resident aquatic organisms. The findings highlight the need for immediate interventions to mitigate anthropogenic impacts and improve water quality. Effective management strategies, including the reduction of pollution and the implementation of municipal water treatment, are essential to restore the lake's ecological balance and ensure its sustainability for future generations.